Uncovering the Drivers of Utility Performance: Lessons from Latin America and the Caribbean on the Role of the Private Sector, Regulation, and Governance in the Power, Water, and Telecommunication Sectors - Andrés, LuisA. (World Bank, 2015)
This book provides insights into infrastructure sector performance by focusing on the links between key indicators for utilities, and changes in ownership, regulatory agency governance, and corporate governance, among other dimensions. By linking inputs and outputs over the last 15 years, the analysis is able to uncover key determinants that have impacted performance and address why the effects of such dimensions resulted in significant changes in the performance of infrastructure service provision.